Four‐year epidemiological study of extended‐spectrum β‐lactamase‐producing Enterobacteriaceae in a French teaching hospital. (9th August 2013) - Gibold, L.; Robin, F.; Tan, R.‐N.; Delmas, J.; Bonnet, R.; Cantón, R.
Abstract Since the end of the last century resistance to oxyimino β‐lactams has steadily increased in Enterobacteriaceae. In the present work we studied extended‐spectrum β‐lactamase (ESBL)‐producing Enterobacteriaceae strains isolated in the teaching hospital of Clermont‐Ferrand, France, between 2006 and 2009. A total of 1368 ESBL‐producing isolates were collected. Most of these isolates (69%) were CTX‐M‐producing Escherichia coli. During the study, the clinical incidence increased by more than 400%, even in the emergency department, and especially in community‐acquired infections, as is the case elsewhere in the world. Most of the ESBL‐producing isolates remained susceptible to furans and fosfomycin, but only 50% to fluoroquinolons. In conclusion, ESBL‐producing bacteria constantly increased during the study period. Unlike many studies, this increase was associated with the wide dissemination of three different CTX‐M enzymes: CTX‐M‐14, CTX‐M‐15 and CTX‐M‐1.